Major works on the necessity and implementations of PKC in WSN: a beginner’s note - Pathan, Al-Sakib Khan (Auerbach Publications, CRC Press, Taylor & Francis Group, 2011)
A wireless sensor is a small, low-cost, low-powered device with sensing, wireless communication, and computation capabilities. While the tiny size and low cost of sensors make them lucrative for use in various applications and services, the constraints associated with those also curb exploitation of computation intensive tasks. This in fact comes as the major concern while thinking about using public key cryptography (PKC) in wireless sensor network (WSN). Within the last few years, we have seen a steep growth of research works addressing various aspects of security in wireless sensor networks. While most of the works suggest using symmetric key cryptography, a good number of works also present their success stories of using PKC in WSN. In this chapter, we present a survey on these noteworthy implementations done so far in this area. Alongside presenting the survey of the significant implementations, we also give an overview of PKC, discuss why and how it is needed for WSN, and the major hurdles to its implementation in WSN.